If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -12 = 4(x + -1) Combine like terms: 20 + -12 = 8 8 = 4(x + -1) Reorder the terms: 8 = 4(-1 + x) 8 = (-1 * 4 + x * 4) 8 = (-4 + 4x) Solving 8 = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 8 + -4x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 8 + -4x = -4 + 0 8 + -4x = -4 Add '-8' to each side of the equation. 8 + -8 + -4x = -4 + -8 Combine like terms: 8 + -8 = 0 0 + -4x = -4 + -8 -4x = -4 + -8 Combine like terms: -4 + -8 = -12 -4x = -12 Divide each side by '-4'. x = 3 Simplifying x = 3
| (x-3)(2x-5)+6=2x^2-12 | | -6x-2=4x-1 | | 18w-2-10w+14= | | 6p^4-486p^2= | | 9x^2+27x-7=0 | | 12x^2-6x-3=3-5x | | f(x)=2x^2+20x+49 | | sin(2x-30)=cos(3x+5) | | (-7-3m^3-3m^4)+(-8m-8m^3-m^4)= | | 4z=16-40 | | 4p+6-2p+3= | | x+8*2x-4=1008 | | 2/3x36 | | Jp=1/2 | | -5x^3-2x^2+7x= | | 5y(6z-x)= | | 4x^3(x^5+4x^3-2)= | | 3x+17y=75 | | x^2-5x-41=-8x-13 | | (10p^5-8p^3)+(3p^3+2+5p^5)= | | 6x=25x-2 | | -7x-6(x-6)=-81 | | n^2-2n-56=0 | | 10-2r=-2(1-2r) | | 4x-3=x-1 | | -2x+7(x+8)=16 | | 5(p-1)=2p-5 | | W=(a+R) | | n^2+13n+36= | | 2x-4(-3x+4)=68 | | 28x^3-7x^2+8x-2=0 | | 6x(x)=864 |